Comparison of right ventricular global longitudinal strain between pacemaker lead position in patients with permanent pacemaker - Fakhri, Muhamad; Rasyid, Hauda El; Yanni, Mefri; Machmud, Rizanda (The Indonesian Heart Association, 2025)
Background: The implantation of a permanent pacemaker (PPM) can reduce right ventricular function. Echocardiography using speckle tracking can detect a decreasing in right ventricular function earlier. The value of right ventricular global longitudinal strain (RVGLS) based on the location of the pacemaker lead between the apex and non-apex was currently unknown, although the placement of the correct pacemaker lead location was very important for evaluating right ventricular dysfunction to prevent right heart failure. This study aims to determined the comparison of RVGLS between pacemaker lead position in patients with permanent pacemaker. Methods: This study was a nested case-control study to assess the comparison of RVGLS between pacemaker lead position in patients with permanent pacemaker, who were divided into the right ventricular apex group (RVA) and the non-right ventricular apex group (NRVA). This study used data from the pacemaker registry and medical records of patients who had undergone pacemaker implantation since June 2021. The shapiro-wilk normality test was performed before analyzing all numerical data, followed by an independent t-test or Mann-Whitney test to determine the differences between groups. Results: In this study, there were 38 patients with permanent pacemakers, consisting of 18 samples with RVA group and 20 samples with NRVA group. In this study, no significant differences were found in age, sex, diagnosis, comorbidities, therapy, pacemaker mode, baseline QRS duration, pacing burden, puncture site, and initial echocardiography between of two groups. There was a significant difference in paced QRS duration between the RVA and RVNA groups (160 + 20 ms vs 140 + 28 ms, p=0.024). Based on statistical analysis, there was a significant difference in the value of RVGLS in the RVA group compared to the RVNA group (-14.87+4.48% vs -18.40+3.21%, p=0.015). Conclusion: The position of the apex right ventricular lead resulted in a lower value of RVGLS compared to the position of the non-apex right ventricular lead.